Coordination or Harmonisation? Feasible Pathways for a European Res Strategy beyond 2020. Issue 1 (February 2013) - Resch, Gustav; Gephart, Malte; Steinhilber, Simone; Klessmann, Corinna; del Rio, Pablo; Ragwitz, Mario
With Directive 2009/28/EC, the European Parliament and Council have laid the grounds for the policy framework for renewable energy sources (RES) in the European Union until 2020. The aim of this paper is to look more closely beyond 2020, well in advance, contrasting and analysing potential RES policy options that are currently being discussed. Generally the assessment includes RES in all energy sectors but a topical focus is put on renewable electricity, specifically within the discussion of policy options for a harmonisation of RES support. The results of the policy assessment indicate that cooperation and coordination among Member States appear beneficial to tackle current problems in RES markets, and fruitful for the period beyond 2020. By contrast, "simplistic approaches" to RES policy harmonisation, for example via a uniform RES certificate trading, are not suitable to ensure substantial future RES growth.